2‐Step PLT16‐AST44 method: Simplified liver fibrosis detection system in patients with non‐alcoholic fatty liver disease. Issue 4 (2nd February 2022) - Fujimori, Naoyuki; Kimura, Takefumi; Tanaka, Naoki; Yamazaki, Tomoo; Okumura, Taiki; Kobayashi, Hiroyuki; Wakabayashi, Shun‐ichi; Yamashita, Yuki; Sugiura, Ayumi; Pham, Jonathan; Pydi, Sai P.; Sano, Kenji; et al.
Abstract: Aim: Accurate detection of the hepatic fibrosis stage is essential to estimate the outcome of patients with non‐alcoholic fatty liver disease (NAFLD). Many formulas, biomarkers, and imaging tests are being developed to predict advanced liver fibrosis without performing a liver biopsy. However, these tests do not have high efficiency in detecting early‐stage hepatic fibrosis. Therefore, we aimed to detect the presence of hepatic fibrosis (≥F1) merely by using only standard clinical markers. Methods: A total of 436 patients with NAFLD who underwent liver biopsy were retrospectively enrolled as the discovery cohort (316 patients) and the validation cohort (120 patients). Liver biopsy and laboratory data were matched to extract simple parameters for identifying ≥F1. Results: We developed a novel simplified ≥F1 detecting system, designated as 2‐Step PLT16‐AST44 method, where (1) PLT of 16 × 10 4 /μl or less, or (2) PLT greater than 16 × 10 4 /μl and AST greater than 44 U/L is determined as having ≥F1 fibrosis. The 2‐Step PLT16‐AST44 method had a sensitivity of 68%, a specificity of 90%, a positive predictive value (PPV) of 97%, a negative predictive value (NPV) of 40%, and an accuracy of 72% to detect ≥F1 fibrosis in the discovery cohort. Validation studies further supported these results. Despite its simplicity, the 2‐Step PLT16‐AST44 method's power to detect ≥F1 fibrosis in total NAFLD patients was comparable to hyaluronic acid, type 4 collagen 7S, FIB‐4, and APRI. Conclusions: We propose the 2‐Step PLT16‐AST44 method as a simple and beneficial early‐stage hepatic fibrosis detection system.